Speech Acts Analysis of The Main Characters on Amy Tan's "The Joy Luck Club" - Nanik Mariani; Sulistyo Rini; Adrie Satrio (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
Abstract: This study tries to describe how speech acts are applied through the main character in The Joy Luck Club. It is broken down into: (l) a description of the types of illocutionary speech acts performed, (2) a description of how the speech acts are carried out which is also translated into two sub-objectives, namely: (I) a description of how the illocutionary acts are performed; and (2) a description of how the perlocutionary act was carried out. The description of the types of illocutionary acts is based on Searle's category of illocutionary acts which is also used as a category for the actual meaning of an utterance. While the forms are based on the syntactic form of the sentence. While the perlocutionary act is said to be effective if the speech act has an influence on the thoughts, actions, or feelings of the listener in accordance with what was intended by the speaker. To answer these research questions, a qualitative research design was carried out. Data was collected from the language use of the main characters in Amy Tan's novel, The Joy Luck Club. Then, dialogues, monologues, and actions were collected, breed Sctibed, and analyzed. The results showed that the type and highest meaning used by the main character was representative. Meanwhile, in terms of form, most use declarative. Moreover, the perlocutionary acts produced are mostly ineffective.  Abstract: This study tries to describe how speech acts are applied through the main character in The Joy Luck Club. It is broken down into: (l) a description of the types of illocutionary speech acts performed, (2) a description of how the speech acts are carried out which is also translated into two sub-objectives, namely: (I) a description of how the illocutionary acts are performed; and (2) a description of how the perlocutionary act was carried out. The description of the types of illocutionary acts is based on Searle's category of illocutionary acts which is also used as a category for the actual meaning of an utterance. While the forms are based on the syntactic form of the sentence. While the perlocutionary act is said to be effective if the speech act has an influence on the thoughts, actions, or feelings of the listener in accordance with what was intended by the speaker. To answer these research questions, a qualitative research design was carried out. Data was collected from the language use of the main characters in Amy Tan's novel, The Joy Luck Club. Then, dialogues, monologues, and actions were collected, breed Sctibed, and analyzed. The results showed that the type and highest meaning used by the main character was representative. Meanwhile, in terms of form, most use declarative. Moreover, the perlocutionary acts produced are mostly ineffective. Keywords:  Speech Act, Type, Meaning, Form, Illocutionary Act,